Implementasi Pembelajaran Akidah Akhlak Berbasis Nilai-Nilai Pendidikan Profetik sebagai Upaya Pengembangan Karakter Siswa di YPP MA Islahul Ummah NW Dasan Aman - Wahid, Lalu Abdurrahman; Rizal, Muh. (Lembaga Yasin AlSys, 2025)
Moral and character degradation among students remains a serious challenge in education, as reflected in undisciplined behavior, low responsibility, and limited spiritual awareness. Consequently, teachers are expected not only to emphasize cognitive aspects but also to integrate prophetic values into learning to shape students into faithful, virtuous, and responsible individuals. This study aims to describe the implementation of prophetic education values in Akidah Akhlak learning and to analyze their relevance to character development. A descriptive qualitative approach was employed, with data collected through non-participant observation, semi-structured interviews, and documentation. Data analysis was conducted through reduction, presentation, and verification stages, with credibility tested using source and technique triangulation. Informants were selected through purposive sampling. The findings show that the implementation of prophetic education values at MA Islahul Ummah Dasan Aman is carried out through curriculum integration, teacher role modeling, and the reinforcement of prophetic values in Akidah Akhlak learning. Its relevance is evident in the alignment of learning objectives with prophetic education, the integration of prophetic values into subject matter, teaching methods that reflect prophetic principles, curriculum objectives, learning strategies, and supportive learning environments. The study affirms that prophetic education plays a significant role in character development through Akidah Akhlak instruction.